Lowering the threshold : reducing the cost and risk of private direct investment in least developed, small and vulnerable economies - Hughes, Anthony (2002)
Examines the proposal for the replacement of trade preferences by investment preferences, which was made in a paper to the St. Lucia Meeting of the Commonwealth Secretariat/World Bank Task Force on Small States. Makes the point that trade preferences had always been intended to persuade investors to locate enterprises in the preference-receiving economies.